Tüp sistemlerin kesin ve yaklaşık yöntemle hesap sonuçlarının karşılaştırılması - Ayık, Bahadır (Fen Bilimleri Enstitüsü, 1997)
Kentlerde "gr§âJna%etterinin artması aynı bir arsa alanına daha çok inşaat alanı yapmayı gerektirirken bir yandan da yüksek bina yapımı bir teknoloji, güç ve prestij yansı olarak ilgi çekmektedir. Hangi nedenle olursa olsun, mühendis gitgide daha yüksek bina projelendirilmesi isteği ile karşılaştığından çözüm yollan aranöıakta, bir yandan malzeme kalitesi yükseltilirken öte yandan yatay yüklere karşı en uygun sistemler aranmaktadır. Ülkemizde de yaygınlaşmakta olan yüksek binaların taşıpcj_jisj^nlerinin en önemli bölümü

The framed-tube structure is now widely accepted as an economic solution for tall structures of both steel and concrete. In its basic form, the system consists of closely spaced exterior columns tied at each floor level by spandrel beams to produce a system of four orthogonal rigidly jointed frame panels forming a rectangular tube system ( Fig. la ). ( Fig. la ) Framed Tube Real Structure The behavior of a framed-tube is more complex than that of a simple closed tube and the stiflhess is less. In addition to the cantilever bending action, which produces tensile and compressive stresses on opposite faces of the tube, the side frames undergo the usual plane-frame shearing action in each story under the action of lateral forces. This primary action is complicated by the fact that the flexibility of the spandrel beams produces a shear lag which has the effect of increasing the axial stresses in the corner columns, and of reducing them in the inner columns of the normal panels. The latter effects will produce warping of the floor slabs, and consequent deformations of interior partitions and secondary structure which must be considered in the design. It is important to asses both the warping effect and the degree of sway caused by lateral forces, since either may control the design of the structural system. Although it is theoretically possible to analyze the structure by matrix techniques using standard three-dimensional framework programs, the system is generally too complex for a direct solution on existing computers. By recognizing the dominant mode of behavior of the structure, it has proved possible to reduce the three-dimensional system to an equivalent plane frame with a consequent large reduction in the amount of computation required. These simplified methods recognize that the lateral loads are resited by two main actions. The rigidly jointed side frames undergo shearing deformations, while the normal frame panels undergo axial deformations of the columns, the uniformity of which will depend on the relative stiffness of the spandrel beams. The interactions between the side and IX normal panels consist mainly of vertical shear forces, and different forms of fictitious elements have been introduced to effect the vertical shear transfer that occurs. Even allowing for the reduction in the size of the problem which may be afforded by the symmetry of the structure, these simplified methods still require the services of a digital computer of a reasonable size to obtain a solution. These appears to be a distinct need for an even simpler method that can be used in the early stages of design to give a reasonable assesment of the structural behavior, and allow preliminary evaluations of the main structural element sizes to be made. A very simple method of analysis is given in this study with the ideas below which will be the theorical basis of the approximate solution of the tube system under lateral forces. In the framed-tube structure shown in Fig. la, the lateral load is resisted primarily by the following actions : (1) The rigidly jointed frame actions of the shear-resisting panels parallel to the load (ABandDC); (2) the axial deformations of the frame panels normal to the direction of the load (AD and BC); and (3) the axial forces in the discrete corner columns. The interactions between the normal and side panels consist mainly of vertical interactive forces along corners A, B, CandD. The high in-plane stiffness of the floor slabs will tend to restrict any tendency for the panels to deform out of plane, and it is assumed that these secondary effects may be neglected in comparison with the primary actions. Only in-plane effects need then be considered in each panel. The spacing of the beams and columns are assumed uniform throughout the height, as is usually the case in practice. In addition, to simplify the expressions in the analysis, it is assumed that both beams and columns are of uniform section throughout the height. This is not strictly necessary, and it is straightforward to extend the analysis to include a number of regions in which the beams or columns have constant stiffness. It is then assumed that each framework panel of columns and spandrel beams may be replaced by an equivalent uniform orthotropic plate, to form a substitute closed-tube structure (Fig. lb). IE (Fig. lb) Framed Tube Substitute Structure The properties of the orthotropic plate must be chosen so that the two elastic moduli .in the horizantal and vertical directions represent the axial stiffiiess of the beams and columns, respectively, and the shear modulus represents the shear stiffiiess of the framework. The equivalent tube composed of orthotropic plate panels is shown in Fig. 2, in which the stress system on a small element on each face is given. nrriijinrr ttttt; (Fig. 2) Notation for Stresses To reduce the three-dimensional frame-tube system to an equivalent plane frame with a consequent large reduction in the amount of computation required, various approximate methods offered. The numerical solutions and the results obtained from the analysis method shows that the general character of the distribution of the stresses in the columns of the normal panels are as shown in Fig 3. (Fig 3) Distribution of the stresses in the columns of normal panels XI In the last twenty years, several structural systems have been developed to minimize cost premiums for building height. These include tubular, tube-in tube, and bundle-tube systems involving reinforced concrete and structural steel construction. It has also been found that one of the most effective ways to minimize costs in tall building construction is through composite or mixed steel-concrete construction, in which the most desirable contributes of each material are utilized and the disadvantages eliminated. In this process, elements of concrete systems, such as the shear walls and punched framed tubes, have been recognized as efficient elements to resist wind forces and to provide lateral rigidity. The use of these elements with simple structural steel framing, especially for floor framing, offers advantages of economy and speed. The object of combinations has been to utilize the rigidity of concrete for lateral load resistance, and the lightness and spannability of steel in floor framings. As the construction methodology of such mixing of system was established and accepted by the construction industry, their use became widespread, which spurred further refinements and developments. Thus mixed steel-concrete systems gained popularity and acceptance as viable alternative to both structural steel and reinforced concrete buildings. In current practice, it is almost customary to offer three choices-steel, concrete, and composite systems - for cost and system evaluations for a high-rise building. Since there are numerous types of suitable members in both reinforced concrete and structural steel, a variety of practical combinations can be derived that serve and meet the overall structural performance criteria. Resistance to wind has been the prime consideration in system design since, until recently, tall buildings were mostly built in nonseismic areas. In recent years, however, there has been a growing interest in using the efficient structural systems developed for wind resistance to build tall earthquake - resistant structures economically. A framed tube system consists of closely - spaced exterior columns tied at each floor level with deep spanderel beams, thereby creating an effect of a hollow concrete tube perforated by window openings. From a structural point of view, the tubular system combines the behavior of a flexural cantilever such as a slender shear wall, with that of a beam - column frame. The over turning under lateral load is resisted by the tube form causing compression and tensison in yhe columns, while the lateral shear is resisted primarily m the frames on the two sides of the building parallel to the direction of lateral loads. This is illustrated in (Fig. 4). In modern tubular buildings, limiting lateral drift controls design more often than the strength requirements. And it is considered necessary to keep a proper balance of stiffnesses between spandrels and columns so that these elements are efficiently utilized to provide lateral stiffness. From a seismic perspective, a framed tube can be designed to act as a three- dimensional ductile moment frame wherein the exterior and columns and spandrel beams are the elements resisting the seismic and the tributary vertical loads. Designing strong columns and weak beams is considered essential to the survival of a ductile frame subjected to strong ground motion. There are four major considerations that are fundamental to the design of a ductile moment frame columns and beams: 1. The columns is each story are designed to resist story shear. 2. At any joint, column flexural strength is greater than the beam flexural strength. 3. Spandrel beams are designed to meet strength and ductility requirements for resistance to vertical and lateral loads. Beam stiffnesses are provided to meet drift requirements for the framed tube. Xll 4. Column reinforcement detailing must prevent brittle shear and compression failure. Little information is available on the feasibility of framed tubular building in seismic regions. There is a concern that the framed tube systems with deep spandrels may not meet the strong - column weak - beam requirement and that plastic hinging in beams may preceed the column hinge formation, adversely affecting structural stability. (Fig 4) Normal stresses of columns in a tube system In this study we examined one of the offered approximate method and used it in the calculations. This approximate method takes the normal panel frame as an equivalent column added to the corner column of the side panel and tries to find the parameters that gives the distribution of the axial stresses in the normal panels. Comparing the exact solution results with the approximate method results we saw that the approximate method can be used in the early stages of design to give a reasonable assessment of the structural behavior, and allow preliminary evaluations of the main structural element sizes to be made.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1997
Keywords: Arazi değeri; Betonarme yapılar; Taşıyıcı sistemler; Yatay yükler; Çelik yapılar; Çerçeve sistemi; Land valuation; Reinforced concrete structures; Supporting systems; Horizontal loads; Steel structures; Frame system